A novel winding structure in planar inductors to decrease the overall capacitive couplings - Shahabi, N.; Boora, A.; zare, F.; Ledwich, G.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2010)
This paper presents a new method for winding configuration in planar magnetic elements with more than two layers. It has been proven by 3D Finite Element method and mathematical modelling that this suggested configuration results in reduction of the equivalent capacitive coupling in the planar inductor.